2011
DOI: 10.1016/j.neuroimage.2010.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality estimation for optimal detection of functional networks in BOLD fMRI data

Abstract: Estimation of the intrinsic dimensionality of fMRI data is an important part of data analysis that helps to separate the signal of interest from noise. We have studied multiple methods of dimensionality estimation proposed in the literature and used these estimates to select a subset of principal components that was subsequently processed by linear discriminant analysis (LDA). Using simulated multivariate Gaussian data, we show that the dimensionality that optimizes signal detection (in terms of the receiver o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
(75 reference statements)
4
31
0
Order By: Relevance
“…This is consistent with prior analyses of Yourganov et al [43], who found that ICA detection of brain networks underperforms, relative to linear discriminant methods. This may be partly due to the PCA-based dimensionality estimation method used in MELODIC.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with prior analyses of Yourganov et al [43], who found that ICA detection of brain networks underperforms, relative to linear discriminant methods. This may be partly due to the PCA-based dimensionality estimation method used in MELODIC.…”
Section: Discussionsupporting
confidence: 91%
“…The comparison of the eigenvalues to those obtained from surrogate data on the other hand provided a reasonable, rough estimate to guide the choice of dimensionality. Other dimensionality estimation approaches, such as those used in activation studies (Yourganov et al, 2011) or ICA (Varoquaux et al, 2010), could be adapted to dynamic FC and evaluated in future studies. The ten first eigenconnectivities used for further analysis did not use the full "signal space" and explained 34% of the variance in dynamic FC, but our results suggest that they captured important differences between the groups.…”
Section: Methodological Limitations and Future Directionsmentioning
confidence: 99%
“…The demeaned residuals were then subjected to Multivariate Exploratory Linear Optimized Decomposition into Independent Components (MELODIC) using FSL. We initially used the Laplace approximation to the Bayesian evidence of the model order to determine the number of components, but the length and resolution of the scans produced hundreds of components that proved impractical for analysis, as noted previously (Yourganov et al, 2011). Consequently, we selected 25 components for resting and ‘fall asleep’ scans based on previous dual regression studies (Filippini et al, 2009).…”
Section: Methodsmentioning
confidence: 99%